Quantitative reconstruction of Early Cretaceous dune morphology in the Ordos paleo-desert and its paleoclimatic implications - Cao, Shuo; Ma, Jing; Zhang, Laiming (Frontiers in Earth Science, 2023)
Deserts are among the most important terrestrial sedimentary environments and have existed in all periods throughout Earth history. In contrast to modern deserts, the ability to quantitatively evaluate the area and desertification degrees of ancient deserts is limited due to the lack of unambiguous proxies. Dune morphology and their spatial arrangements directly reflect the degree of desertification of deserts. Recently, a methodology for obtaining the morphological parameters of dunes was established, although it has not been applied to ancient dunes and deserts in deep time. In the Ordos Basin, both the Early Cretaceous desert and modern deserts (Hobq Desert and Mu Us Desert) were well developed and exposed, which makes the Ordos Basin an ideal place to quantitatively evaluate the paleo-desert based on the proposed methodology. In this study, a total of 698 and 1490 morphological parameters reflecting the Early Cretaceous desert and modern deserts in the Ordos Basin were obtained, respectively. For the Ordos paleo-desert, our results show that its area was larger and its degree of desertification was more severe than those of modern mid-latitude deserts, including the modern desert in the Ordos Basin, but were similar to those of the modern low-latitude deserts. Our results, therefore, suggest that the Ordos paleo-desert was a nonnegligible and large desert during an interval of Earth’s history. Since the other controlling factors, such as regional geography and sources of both the ancient and modern deserts in the Ordos Basin, have remained nearly unchanged, we speculate that it may have been the relatively high temperature, high levels of atmospheric carbon dioxide and relatively low precipitation during the greenhouse period (i.e., Early Cretaceous) that led to the large area and severe degree of desertification of the Ordos paleo-desert.